lonospheric propagation of Atmospherics - CRIPLONKAR, M. W.; RATTIANGADI, M. S. (MAUSAM, 1963)
With the equipment described in an earlier communication numerous waveforms of atmospherics in the frequency region 50 c/s to 300 kc/s have been reported at this station during the period April 1957 to December 1958. A large number of these show a multi-hop propagation and the results of measurements of these waveforms are analysed and presented in this paper. It is found that the height of the reflecting layer varied from about 55 km to about 120 km but most frequently it lies between 80 and 90 km. The frequency distribution curve of height is skew and has a tendency to show Gaussian distribution around two values, viz., 60 and 90 km. Similarly the distance of the source of atmospherics varied from about 200 to 2000 km. The frequency distribution curve in this case shows principal peaks at about 750 and 1750.km with subsidiary peaks on either side of these. This trend is also shown by the individual monthly histograms for distances. Further, when separate histograms were drawn for distances which were associated with a height of 60 km and those that were associated with a height of 90 km it was found that the two principal peaks at 750 and 1700 km were prominently shown by the 90-km group alone and only the first peak was shown by the 60-km group, thus indicating a preponderant role of the upper layer. This statistical distribution of distances has been interpreted qualitatively with the help of Holingworth interference pattern of field strength. When heights of there refraction layers are plotted against the corresponding source distances, it is seen that the height increases rapidly at first and then gradually reaches a limiting value around 15 km. However, other evidence shows that there exist two reflecting layers, one at about 60 km and the other at about 90 km. The reflection coefficient of the ionosphere varied from 0.4 to 0.9 or more. Occasionally even smaller values upto 0.25 were also observed. The reflection coefficient is higher in winter than in summer.